Hubungan Antara Indeks Massa Tubuh Dan Volume Ekspirasi Paksa Detik 1 (VEP1) / Kapasitas Vital Paksa (KVP) Pada Pasien PPOK Stabil Derajat 2 Di Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta - Damayanti, Junia Astri (2016)
Background : Decrease in body cell mass is one of the systemic manifestations of COPD. Changes in body cell mass known through weight loss and reduction in fat-free mass. Weight loss has a negative influence on the structure, elasticity, lung function, respiratory muscle strength and endurance, immune defense mechanisms of the lungs, and breathing. Body Mass Index (BMI) is one of the parameters used to determine the criteria for the proportion of a person's body. BMI correlated with the total amount of fat the human body. It can describe a person's weight status. The purpose of this study was to determine the relationship between Body Mass Index (BMI) and Forced Expiratory Volume in 1 second (FEV1) / Forced Vital Capacity (FVC) in patients with stable COPD grade 2. Methods : This research is an analytic observational study with cross sectional approach. Respondents that used for this research as many as 37 people were selected using purposive sampling techniques. Data analysis was done by computerized using Pearson correlation test. Results : Body Mass Index (BMI) Most of this research is 20.87 and Forced Expiratory Volume in 1 second (FEV1) / Forced Vital Capacity (FVC) was 71.37. Statistical analysis showed p value = 0.032 by Pearson correlation 0.307. Conclusion : There is a significant correlation between Body Mass index (BMI) and Forced Expiratory Volume in 1 second (FEV1) / Forced Vital Capacity (FVC) in Patients with Stable COPD Grade 2 at The Center for Lung Health Community Surakarta.